COVID-19 and Turkish University Students With Visual Impairments: An In-Depth Inquiry. (November 2022) - Sarica, Ayşe Dolunay; Ulu-Ercan, Elif; Coşkun, Umut Haydar
Introduction: The purpose of this study was to investigate the effect of COVID-19 on the academic life, psychological well-being, social relations, and physical health of university students with visual impairments via their personal judgments.Methods: A qualitative research design was utilized with 19 participants studying at 10 Turkish universities located across seven cities. Personal online semi-structured interviews were held in January 2021. The audio-taped qualitative data were analyzed deductively in light of four predetermined themes: academic life, physical health, psychological well-being, and social relations.Results: Findings revealed the negative effects of the lockdown on daily and, specifically, campus life. Most participants claimed their preference for traditional over online education due to certain academic, psychological, and social difficulties, stating also that campus life had many academic and social advantages compared to online education. Physical health issues including access to medical treatments and lack of activity/mobility were also stressed.Discussion: It was interesting to observe that despite the interviews' focus on daily life, students provided views on the benefits of traditional education and how and why their individual needs should be met by universities, much more than expected.Implications for Practitioners: It may be concluded that several developmental domains of students with visual impairments are affected by attendance at a university and that offices of disability services of higher education institutions and university counseling centers should take thoughtful actions to meet the specific needs of this student population tailored to both online and traditional education.